ANALISIS PENGARUH BEBERAPA FAKTOR TERHADAP “FARMER SHARE”PADA SISTEM PEMASARAN KOPI ARABIKA DI KABUPATEN BENER MERIAH PROVINSI ACEH - Mustafa Usman (Jurnal Bisnis Tani, 2016)
The purpose of this research is to know the size influence of sale volume, selling price, and marketing margin to farmer’s share on the Coffee Arabica marketing system in Bener Meriah District. The Decision of territory sample is done in purposive sampling method, namely Bandar District and Bukit District. The result of analysis shows us that sale volume and selling price product give us the positive influence significant to farmer’s share, yet marketing margin gives them negative influence to farmer’s share or profit margin Coffee Arabica farmer’s in Bener Meriah Ditrict. The selling price of product constitutes the most dominant factor that influence the farmer’s share, then follows by selling volume and marketing margin. It is suggested to the Coffee Arabica farmer in order they are able to enlarge the scale of their farm and improve the quality and their productivity in order to increase the selling volume and selling price product, and they could also squeeze the expenses of marketing through the system of choosing the marketing channel that is more exact, so that they could enlarge the farmer’s share at Coffee Arabica farmer’s in Bener Meriah District. To concrete this implication, we suggest the government to give our farmers some capitals and to guide, contribute and counsel them in order for them to be more skillful and motivated in Coffee Arabica farming. Al last they can increase their income and welfare sustainably.